The Use of Technology in Quarantine: A Way to Maintain and Promote Physical Health - Rahman Sheikhhoseini; Parisa Sayyadi; Hashem Piri (New Approaches in Sport Sciences)
Background: Along with the outbreak of coronavirus and quarantine practices in many countries, physical activities have certainly been severely restricted. The purpose of this review was to investigate the role of technology in maintaining and improving physical health. Method: For this systematic review study, the research method in this study included searching on PubMed and Google Scholar databases. Articles written in English and Persian in peer reviewed journals that examining the effect of electronic games and virtual reality on physical fitness were selected for analysis. Then, the eligible studies classifieds based on the study population ages. Results: Of 12563 studies found, 14 studies were eligible to enter the study. Research has shown that the use of technology significantly affect gait, balance, strength, flexibility, and mental functioning of the elderly, as well as balance, strength, endurance, and cognitive abilities in adults and children's physical endurance. Conclusions: According to studies under review, the use of technology has a significant effect on improving and maintaining the physical and mental fitness of people in different ages. So, we can suggest using exergame and virtual reality exercises as a possible intervention to promote and maintain physical and mental fitness in quarantine.